2010
DOI: 10.1186/1477-7827-8-15
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent role of steroids in the regulation of growth of the hen follicular wall

Abstract: BackgroundThe ovaries are the primary targets of senescence effects in mammalian and avian species. In the present study, relationships between reproductive aging, sex steroids and the growth pattern of the pre-ovulatory follicle wall were investigated using young hens with long clutch (YLC), old hens with long clutch (OLC), old hens with short clutch (OSC), and old hens with interrupted long clutch (OILC).MethodsExperiment 1: Hens were sacrificed 1.5 and 14.5 h after ovulation. Experiment 2: YLC and OILC hens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Furthermore, concentrations of androgens used to stimulate these cells were quite high. Thus, androgenic effects on follicle development may be concentration-and age-dependent, consistent with reports of age-dependent differential effects of hormones and growth factors (46,47). For our studies, we did not use prepubertal animals because prepubertal GC-specific ARKO animals still had normal follicular development (13).…”
Section: Nonspecific) (D-f)supporting
confidence: 79%
“…Furthermore, concentrations of androgens used to stimulate these cells were quite high. Thus, androgenic effects on follicle development may be concentration-and age-dependent, consistent with reports of age-dependent differential effects of hormones and growth factors (46,47). For our studies, we did not use prepubertal animals because prepubertal GC-specific ARKO animals still had normal follicular development (13).…”
Section: Nonspecific) (D-f)supporting
confidence: 79%
“…Interestingly, similar to MT2, GnIHR was also found to be expressed in both the thecal and granulosa layers32. It has been reported that E2 secretion and GnIHR expression regulate egg production and quality33343536. GnIHR is mainly expressed in the pituitary.…”
Section: Discussionmentioning
confidence: 87%
“…The reproductive performance of chicken females is known to deteriorate in accordance with age .The ovaries and particularly the follicles are the primary targets of senescence (Lebedeva et al, 2010). Various factors are associated with the initiation of the gradual decline in egg production in a flock of aging birds, which include the different sizes of yolk follicles as well as the changes in the pattern of yolk accumulation into the follicle and the high rate of atresia in the small follicles in addition to the slight transfers of follicles into rapid growth phase among old hens (Oguike et al, 2006).…”
Section: Introductionmentioning
confidence: 99%